الأبعاد النظرية للتقريب بين المذاهب الأصولية : دلالة الألفاظ نموذجا - راضية، باشوش (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
The research undertakes the study of the issue of convergence between the different schools of jurisprudence by adopting significance of words (semantics) as the model. The researcher exhibits the concept of convergence. its guiding rules. the juristic methodology as per semantics. with an explanation of the relevance of Usul (Islamic jurisprudence) in bridging the divergence of the different Muslim jurists. Also the researchers elucidate the perspective of convergence of the schools with the aid of semantics. To do this. the researcher adopted the inductive approach in the collection of the required data. while exercised the analytical method in highlighting the Hanafi and the view of the majority of Muslim jurists towards general semantics. Finally. the research adopted the comparative method in investigating the different views of the jurists. the point of their divergence and the point of their agreement. The research concludes that. convergence is possible. but there is a need for Muslim jurists to put efforts together for possible convergence between the schools for the achievement of the higher purpose of maqasid Shari'ah (the higher purpose of the Islamic law) as outlined in the Quranic verse: "And verily! This your religion (of Islamic Monotheism) is one religion. and I am your Lord. so keep your duty to Me"(Al-Mu'minun: 0 t ).